CLIMATE CHANGE AND INTERNATIONAL LAW: REVIEWING COMMITMENT FROM ASEAN AND EU - Sabatira, Febryani; Knudsen, Gustav; Saputra, M. Febriyan (Sriwijaya Crimen and Legal Studies, 2023)
Climate change is a major issue occurring in our time. Global in scope and unprecedented in size, the repercussions of climate change include everything from changing weather patterns that endanger agricultural production to increasing sea levels that raise the possibility of catastrophic flooding. Considering the broad impact of climate change, all parties must take any measure necessary to address this issue, including primary regional organizations, namely the Association of Southeast Asia Nations (ASEAN) and the European Union (EU). This study examines the approach of ASEAN and the European Union regarding climate change that dramatically impacts the country's stability. Research shows that ASEAN-EU cooperation on climate change consists of 3 (three) main collaborations, namely Green Growth and the Environment, ASEAN-EU Statement on the Paris Agreement Reaffirming Commitment to Cooperation to Address the Shared Challenges of Climate Change, and The Second EU-ASEAN High-Level Dialogue on Environment and Climate Change. These forms of cooperation emphasize the commitment of the European Union as an advanced regional organization to support ASEAN in dealing with the impacts of climate change and implementing policies to reduce the use of carbon gas. In addition, the comparison of ASEAN and European Union policies on climate change ASEAN and the European Union is based on indicators according to Article 4 of the UNFCCC, which consists of progress, reduction of carbon gas emissions and greenhouse effects, adaptation and mitigation, and implementation of national policies. In addition, it can be seen that ASEAN policies are more in the form of a framework in conferences that reduce various regulatory instruments with each focus. At the same time, the European Union uses an approach in the form of an action plan that will be integrated into one law on climate change, namely the European Climate Law.